1999
DOI: 10.1021/om980814c
|View full text |Cite
|
Sign up to set email alerts
|

New Structural Motifs in Metallaborane Chemistry. Synthesis, Characterization, and Solid-State Structures of (Cp*W)3(μ-H)B8H8, (Cp*W)2B7H9, and (Cp*Re)2B7H7 (Cp* = η-C5Me5)

Abstract: Hydrogen loss from the 7 skeletal electron pair (sep) nido 2-Cp*H3WB4H8, 1 (Cp* = η-C5Me5), the metal analogue of pentaborane (9), has been examined as a potential source of unsaturated, reactive species. Pyrolysis of 1 leads to 6 skeletal electron pair (Cp*W)2B5H9, 2 (45%), 7 sep Cp*3W3(μ-H)B8H8 3 (19%), and 7 sep (Cp*W)2B7H9, 4 (low yield), whereas photolysis gives 2 (52%) and 4 (7%). Compound 2 is known, and 3 and 4 have been spectroscopically and crystallographically characterized. Further, the isoelectron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
39
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 52 publications
3
39
0
Order By: Relevance
“…These compounds establish a new set of cluster geometries remarkably different from the canonical deltahedra of the [B n H n ] 2À boranes that underpin the clusterelectron counting rules. [19,20] The oblate cluster shapes, high metal-coordination numbers, and cross-cluster bonds featured support the idea that variation in the transition metal can drive a change from borane-to boride-like bonding.Subsequent to the isolation of [(Cp*Re) 2 B 7 H 7 ] from the reaction of [Cp*ReCl 4 ] and monoboranes, [15] we found that it is formed in a more straightforward manner from the reaction of [(Cp*ReH 2 ) 2 B 4 H 4 ] with BH 3 …”
mentioning
confidence: 91%
See 2 more Smart Citations
“…These compounds establish a new set of cluster geometries remarkably different from the canonical deltahedra of the [B n H n ] 2À boranes that underpin the clusterelectron counting rules. [19,20] The oblate cluster shapes, high metal-coordination numbers, and cross-cluster bonds featured support the idea that variation in the transition metal can drive a change from borane-to boride-like bonding.Subsequent to the isolation of [(Cp*Re) 2 B 7 H 7 ] from the reaction of [Cp*ReCl 4 ] and monoboranes, [15] we found that it is formed in a more straightforward manner from the reaction of [(Cp*ReH 2 ) 2 B 4 H 4 ] with BH 3 …”
mentioning
confidence: 91%
“…Subsequent to the isolation of [(Cp*Re) 2 B 7 H 7 ] from the reaction of [Cp*ReCl 4 ] and monoboranes, [15] we found that it is formed in a more straightforward manner from the reaction of [(Cp*ReH 2 ) 2 B 4 H 4 ] with BH 3…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The convenient synthesis of Cp*WH B H in good yield, mentioned above, permitted an examination of its reaction chemistry (34,35). This tungstaborane obeys the electron counting rules*the three hydrides on tungsten providing the three electrons required to make it analogous to CpCoB H (36).…”
Section: Highly Condensed Metallaboranesmentioning
confidence: 99%
“…Hence, we were interested in the consequences of removing one or more of the potentially labile hydrogens. Whatever the initial product, it is not stable and rapidly produces three compounds: Cp We have discussed elsewhere (35) the connection between these compounds and &&hypoelectronic'' clusters found in zintl phases (42) as well as those with large transition metal clusters containing close-packed metal atom cores. Essentially, reduction of the metal electron count collapses a closo structure into a highly capped core of lower vertex number.…”
Section: Highly Condensed Metallaboranesmentioning
confidence: 99%